Goal Setting: A Tool for Motivation - Rozina, Muzammil (2021)
While we all know that motivation is a vital factor for boosting employees’performance, the tools used for achieving this are taken up differently by different researchers and philanthropists. In this article, an attempt has been made to project goal setting exercise as an effective tool for boosting employees’ motivation in an organization’s performance management system (PMS).